ON THE SPECTRAL AND PHOTOMETRIC ACTIVITY IN YOUNG STARS - Ismailov, N. Z. (Одеські астрономічні публікації, 2017)
Results of long time homogenous medium resolution spectral observations of classic T Tauri type stars DI Cep, T Tau and GW Ori obtained during 1972-1990 are analyzed. Weak correlation with on metallic absorption lines of optical spectrum spectral types and equivalent widths of hydrogen lines is discovered. It is showed that spectral types of these stars are varying during observation seasons in different ranges. More wide range of variations of spectral types, is observed in DI Cep - F4-K5V, are of all 21 subtypes, in GW Ori - F3-G5V, are of all 13 subtypes and T Tau - G1-K5V, are in all 9.5 subtypes. Observational photometric and spectral properties of these stars may be explained by formation of hot (in case of DI Cep) and cool (in case of GW Ori and T Tau) spots on these stars. We are suggesting that simultaneously a presence of variable circumstellar dust may also be a cause of variability of following two stars.